A shared moment: antipoverty policy under the New Democrats and New Labour, 1992-2005 - Lilly, Alice Olivia Louise (2017)
This thesis seeks to answer two research questions. Firstly, building on a small corpus of literature that has identified welfare-to-work programmes as a key commonality between the New Democrats and New Labour, it asks whether there were other common aspects of their antipoverty policies. Drawing on a range of archival sources, as well as a variety of other primary materials, it finds that there were two other key areas of commonality: efforts to ensure the value of work through the use of in-work tax credits and minimum wages; and attempts to reduce teenage pregnancy rates. Both parties, it is argued, saw these three strands of policy as complementary. It is also shown that the specific policies that they implemented in each area were, at times, the result of the active sharing of policies through transatlantic networks of advisors and intellectuals. It is also acknowledged that different national contexts affected the precise nature of these common policies. Secondly, this thesis considers whether this common New Democrat-New Labour approach to poverty might be considered distinctive. Whilst much literature has suggested that both parties hewed to a conservative approach to poverty, or reflected neoliberal ideas, it is argued here that the New Democrats and New Labour presented an approach which, taken as a whole, went beyond the two existing intellectual approaches to poverty—that James T. Patterson has termed “neoconservative” and “structuralist”—and the policies that they generated. Drawing on Daniel T. Rodgers’ concept of a transatlantic “moment” in social policy, it insists on the existence of a distinctively New Democrat-New Labour “moment” on antipoverty policy between 1992 and 2005. Their distinctiveness was rooted in their analysis of the new economy, and the need for antipoverty policy to stress the themes of both responsibility and opportunity.